The Effect of Using Spinning Wheel Media on Students’ Vocabulary Mastery: A Pre-Experimental Research of Third Grade Students at SD Negeri 64 Sungai Raya in Academic Year 2023/2024 - Oktafia, Yuni; Susilawati, Endang; Suhartono, Luwandi (Humanitatis : Journal of Language and Literature, 2025)
Learning media play an essential role in helping students and teachers achieve educational goals. The use of engaging media can enhance the teaching and learning process. In this context, a spinning wheel was used as a tool to introduce and reinforce vocabulary in elementary school, creating a more interactive learning environment. The study aimed to investigate whether Spinning Wheel Media affected students’ vocabulary mastery, specifically among third-grade students at SDN 64 Sungai Raya. This research is a descriptive-quantitative study that employed a pre-experimental design with a one-group pre-test and post-test. Data were collected through a pre-test, treatment session, and post-test. The sample comprised 22 students from Class III A at SDN 64 Sungai Raya. Furthermore, the findings of this research indicated a significant improvement in students’ vocabulary mastery after the treatment. The post-test mean score was 90.2, compared to the pre-test mean score of 39.1. The t-test value was 13.19, and the effect size was 2.8, showing a strong effect. The hypothesis (Ha) was accepted, confirming that Spinning Wheel Media effectively enhanced students’ vocabulary, especially in learning the names of the days of the week.